Transcriptomics insights into glutamine on repairing of histamine-induced Yak rumen epithelial cells barrier damage in vitro - Xiaohong Zhang; Rui Hu; Zhisheng Wang; Junmei Wang; Ziqi Yue; Fali Wu; Wenjuan Zhou; Ali Mujtaba Shah (BMC Genomics)
Abstract Background Glutamine (Gln) plays a pivotal role in maintaining the integrity of the rumen epithelial barrier in mammals. This study aimed to investigate the effects of Gln on histamine-induced barrier damage in yak rumen epithelial cells (YRECs). Results RT-qPCR analysis revealed a significant decrease in the mRNA expression of tight junction proteins (ZO-1, JAM-A, Claudin-1, and Claudin-4) following 24-hour exposure to 20 µM histamine (HIS group) (P < 0.05). In the subsequent experiment, YRECs were first treated with 20 µM histamine for 24 h, followed by 8 mM glutamine for 12 h (HG group). Gln treatment reversed the histamine-induced downregulation of both mRNA and protein levels of tight junction proteins and restored the distribution of ZO-1 at the cell membrane. Transcriptome analysis revealed that co-regulated differentially expressed genes were primarily involved in the mitogen-activated protein kinase (MAPK) signaling pathway and apoptosis. These findings were further corroborated by RT-qPCR, Western blot, and flow cytometry analyses. To determine whether glutamine regulates cell barrier function through the p38 MAPK signaling pathway, 20 µM Skatole, a p38 MAPK agonist, was introduced (SK group). The results showed a significant increase in the p-p38/p38 ratio and a marked decrease in the mRNA and protein expression of tight junction proteins in the SK group compared to the HG group (P < 0.05). Conclusions Glutamine mitigates histamine-induced barrier damage in YRECs through the p38 MAPK signaling pathway and apoptosis regulation.